HAK KONSTITUSIONAL MASYARAKAT PENDUKUNG KOLOM KOSONG TIDAK BERGAMBAR PADA PIKADA CALON TUNGGAL MENURUT UUD 1945 - Ramelan, Ramelan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The implementation of direct regional head elections that have been held several times has given rise to a new phenomenon, namely the emergence of the phenomenon of a single candidate which for the first time appeared in the implementation of the simultaneous regional elections in 2015. This phenomenon eventually gave rise to polemics and debates which could ultimately be resolved through the Constitutional Court's decision which affirmed that regional elections with one pair of single candidates are still carried out with a mechanism of choosing to agree or disagree, which then developed into choosing between blank columns with pictures and blank columns without pictures as an effort to protect the constitutional rights of voters and candidate pairs who have registered. But what is interesting then is the emergence of a follow-up phenomenon in the implementation of the Regional Elections with one pair of candidates, namely the emergence of support groups for blank columns without pictures or empty boxes. The emergence of this group has sparked a new debate regarding whether or not it is permissible for the group to campaign for an empty box victory. This happens because there is expressly no regulation that regulates the rights of the blank column group without pictures to conduct campaigns, both in Law No. 10 of 2016 and in PKPU No. 4 of 2017 concerning campaigns. This phenomenon attracted the author to conduct a research entitled "The Constitutional Rights of the Community Supporting the Blank Column Without Picture in the Single-Candidate Column Pikada According to the 1945 Constitution" by identifying the problem of how the position of the group supporting the blank column without the picture and what rights can be given to the group in the process of electing regional heads which are only attended by one pair of candidates. This study uses a normative-empirical juridical method with an analytical research nature. The data sources used are primary data and secondary data. The data will be analyzed by means of qualitative analysis. The theoretical basis that will be used is the theory of the state of law and the theory of legal certainty. Based on the analysis of the discussion, the author concludes that Law No. 10 of 2016 and PKPU No. 4 of 2017 do not regulate campaign activities that can be carried out by support groups for blank columns without pictures in the implementation of a regional head election. This has ultimately caused a polemic among stakeholders to respond to this phenomenon